PERAN BMT DALAM MENINGKATKAN KEUANGAN MIKRO SYARIAH DI KALANGAN UMKM - Hasriah Hasanuddin (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2025)
BMT or BaitulMaal wat Tamwil is an institution that has two functions, namely Baitul maal or fund house and baitul tamwil or business house. BMT is a sharia financial institution whose job is to store funds from third parties and the channeled to businesses that deserve help and of course profitable. This research aims to explain how the role of BMT in Islamic microfinance among MSMEs. With the existence of BMT, it is able to help the community, especially for MSME business actors. The results of the discussion show that the role of BMT in Islamic finance among MSMEs is very helpful. BMT is able to create decent jobs for the community in terms of capital. BMT provides capital to the community to be used as a business to connect their lives. The financing model carried out by BMT cannot be separated from the principles of sharia. The financing models that can be used are murabahah, musyarakah, mudarabah, and qardhul hasan. Based on this financing model, BMT produces a real impact on its application among MSMEs. The impact is that people do not need to be afraid of business capital anymore. BMT is here to help underprivileged people and make people independent to build their own businesses without having to depend on other people for capital. BMT of course still pay attention to sharia principles by prioritizing usury-free, responsible responsibility, upholding justice and the benefit of Muslims. Keywords : BMT, Sharia Microfinance, MSME